Increasing conspicuity on night-time roads: Perspectives from cyclists and runners. (January 2020) - Fylan, Fiona; King, Mark; Brough, Dean; Black, Alex A.; King, Neil; Bentley, Laura A.; Wood, Joanne M.
Highlights: Night-time pedestrian and cyclist conspicuity is a critical road safety issue. Focus groups explored perceptions and beliefs regarding night-time conspicuity. Limited awareness of best practise for increasing night-time conspicuity. Cyclists and runners prioritise comfort and style over conspicuity in garments. Increasing awareness of night conspicuity and how to enhance it must be a priority. Abstract: Pedestrians and cyclists are at significant risk of being killed as a result of a collision with a vehicle at night-time because of their poor conspicuity. Retroreflective strips positioned on the moveable joints, in a biological motion configuration (biomotion), greatly enhance the night-time conspicuity of pedestrians and cyclists, but it is not clear how widely this strategy is adopted among those running and cycling under low light levels (dawn and dusk or at night). This study explored runners' and cyclists' beliefs about their own conspicuity, and the strategies they use to increase their conspicuity and safety under low light levels. Nine focus groups involving 50 participants (mean age = 39.5 ± 13.9 years) were held with individuals who ran and/or cycled under low light conditions or at night-time. The strategies that participants used to increase their conspicuity and enhance their personal safety, and the importance they placed on increased conspicuity to other road users at night was explored. Data were analysed thematically, with two main themes identified. Strategies describes the different approaches used to increase conspicuity when running or cycling in low light, some of which are ineffective. Importance describes how conspicuity relates to other considerations that influence cyclists and runners. While they may believe that conspicuity is essential for their safety, they may compromise their own conspicuity by prioritising style or comfort, or because they believe that being more conspicuous is of limited value because it cannot compensate for the behaviour of other road users. In summary, cyclists and runners are largely unaware of effective strategies to increase their night-time conspicuity, particularly the use of biomotion reflective strips. Garment manufacturers should ensure that conspicuity features (with supporting educative product information on labels) are incorporated into cyclists' and runners' clothing or accessories to improve wearer conspicuity and hence safety in low light conditions.